Performance assessment of combining rock-bed thermal energy storage and water filled passive solar sleeves for heating Canarian greenhouse. (1st March 2020) - Bazgaou, A.; Fatnassi, H.; Bouharroud, R.; Elame, F.; Ezzaeri, K.; Gourdo, L.; Wifaya, A.; Demrati, H.; Tiskatine, R.; Bekkaoui, A.; Aharoune, A.; Bouirden, L.
Highlights: Combination of two heating systems i.e. rock-bed thermal energy storage and water filled passive solar. This system improves the nocturnal temperature and lead to a reduction in humidity in the greenhouse during the winter season with less fluctuations. The use of combined system covered the heating requirements of the greenhouse. The tomato production can be improved by 49% compared to the conventional greenhouse. Combination of two heating systems is very profitable and could generate profits for farmers. Abstract: During the winter period, in Mediterranean region, the storage and reuse of solar energy in thermal form is an important issue for heating greenhouses. In the present work, the performance of a combination of two systems i.e. rock-bed thermal energy storage and water filled passive solar, for heating canarian greenhouse was analyzed and discussed. The surplus thermal energy available inside the greenhouse was stored in the rock-bed and in the water during daytime for use during cold periods. An experimental study was carried out in two Canarian-type greenhouses, the first is equipped with the combined heating system and the second without. Results show that the combined heating system can improve the nocturnal inside air temperature, during the winter period, by 3–5 °C during clear days and by 2–3 °C in cloudy/rainy days with less fluctuations. A reduction of 10–15% in the air relative humidity was observed in the heated greenhouse during the night. This heating system also improves the substrate temperature during the night by 4 °C on cloudless days and 3 °C on cloudy/rainy days. A very good growth of plants and an increase of 49% of tomato yield has been noted in the heated greenhouse. The thermal energy restored by this system covers a large part of the greenhouse heating requirements. It was also noted that the presence of this heating system lead to a decrease in the development the population of Tuta absoluta in the heated greenhouse. An economic analysis revealed that this system is very profitable and could generate profits for farmers.